Screening for Chlamydia trachomatis in Low-Risk Obstetric Patients. Issue 4 (1994) - Gribble, Robert K.; Ricci-Goodman, Jean M.; Berg, Richard L.
Abstract : Objective: The purpose of this study was to evaluate the prevalence of Chlamydia trachomatis in our rural obstetric population and assess the appropriateness of selective vs. universal prenatal screening. Methods: Between April 1, 1991 and May 1, 1993, 1, 587 patients were screened at their first prenatal visit using a C. trachomatis antigen test. Patients who were unmarried, younger than 20 years of age, or had a history of a previous sexually transmitted disease (STD) were classified as being at high risk for C. trachomatis . All others were considered low risk for C. trachomatis . Results: The overall prevalence of C. trachomatis was 2.0%. There was a significant difference ( P < 0.001) in the 1, 128 patients considered low risk [0.5%, 95% confidence interval (CI) 0.2–1.2] compared to the 459 patients with one or more identifiable risk factors (5.7%, 95% CI 3.7–8.2). Conclusions: Routine prenatal screening for C. trachomatis in our population is not appropriate for low-risk patients.